The Load-Bearing Capacity and Deformability of Connections of Wooden Elements with Composite Materials Based on Fiberglass - Alexander Tusnin; Linkov Nikolay; Klyukin Aleksandr (Buildings)
The research focuses on connections of wooden structural elements with composite materials based on fiberglass. An overview of existing research and regulatory technical documents in the field of connections between wooden elements and composite materials based on fiberglass has been conducted. A type of connection for wooden elements with composite materials based on fiberglass is proposed. The article presents the results of strength and deformability studies of the developed connection. Strength characteristics are established in the form of the slice resistance of the composite material along the welding seam in the connection, a tear resistance of the composite material from the base, and the chipping of the composite material. The deformability characteristics of fiberglass connections under short-term machine testing with linearly increasing load in samples have been determined.